EVOLUTION OF THEORETICAL BASES OF THE STATE FISCAL POLICY - M. A. Ibrahim (Вестник университета)
In this article examines the evolution of views on the category «fiscal policy» in the interpretation of the main economic schools. The basic sources of formation of the state budget, shows the interaction of government spending and taxes, their impact on aggregate demand, economic growth, employment, inflation.